2017
DOI: 10.1093/ckj/sfx007
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of acute cisplatin nephrotoxicity: interest of urinary monitoring of proximal tubular biomarkers

Abstract: BackgroundRenal toxicity induced by cisplatin (CisPt) is a clinical issue in patients with or without chronic kidney disease (CKD). Proximal tubular injury can result in acute kidney injury (AKI), which may compromise the course of chemotherapy and the prognosis. The purpose of this study was to investigate the time course of urinary markers of acute tubulotoxicity and to assess the usefulness of such monitoring in a routine clinical setting.MethodsThis work is an open prospective pilot study carried out among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
2
20
0
3
Order By: Relevance
“…et al study showed that IL-18, NGAL, ITG, and VTN sera levels were significantly increased within a short period of renal injury (within h) and return to the normal levels within few days due to partial regeneration of damaged renal tubules [20]. This may explain the insignificant elevated levels of these biomarkers in the present study.…”
Section: Alkuraishy Et Alsupporting
confidence: 47%
“…et al study showed that IL-18, NGAL, ITG, and VTN sera levels were significantly increased within a short period of renal injury (within h) and return to the normal levels within few days due to partial regeneration of damaged renal tubules [20]. This may explain the insignificant elevated levels of these biomarkers in the present study.…”
Section: Alkuraishy Et Alsupporting
confidence: 47%
“…As shown in Table 3 , the TI of compound ( 2 ) was approximately two-fold higher than the TI of ( 1 ), further suggesting that ( 2 ) has the greatest potential as a cancer-targeting treatment. However, the TI of cisplatin was found to be higher than either ( 1 ) or ( 2 ), despite the platinum drug having significant known side effects in vivo [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, many previous studies reported that Cisplatin is nephrotoxic at the lower end doses of the therapeutic range for clinical use. Acute tubular necrosis, cystic tubular dilatation, tubular regeneration, and renal tissue inflammation were reported when Cisplatin was administered into rats at a dose 7.5 mg/kg of body weight [45]. Other researchers administered a low dose of Cisplatin (0.4 mg/kg) into rats daily for 8 weeks and it resulted in an irreversible kidney injury of acute tubular necrosis, a severe atrophy of glomerulus, and marked dilation of proximal convoluted tubules [46].…”
Section: Discussionmentioning
confidence: 99%